STRATEGI PUBLIC RELATIONS PT INDOTAMA KARYA GEMILANG DALAM MENINGKATKAN PEMAHAMAN PROSES PROSEDURAL TENAGA KERJA INDONESIA - Mareta Puri Rahastine; Silvina Mayasari; Natasha Sasmita (Universitas Bina Sarana Informatika, 2019)
Indonesian Workers (TKI) are domestic workers who work abroad. TKI is the largest foreign exchange earner for Indonesia. For official migrant workers, they will receive employment training conducted at the Overseas Employment Training Center which is managed by Indonesian Manpower Services Distributors as their suppliers abroad. Since the height of the news about Human Trafficking / non-procedural human trafficking has become a special concern by the Indonesian government, various ways of prevention are carried out by the government together with related official institutions. The author uses descriptive-qualitative research method, which is done by direct observation and in-depth interviews with the parties concerned, and the data collected later on analysis by descriptive analysis by describing the results of research in the form of research reports. With the holding of campaigns by the government and related institutions such as that carried out by PT Indotama Karya Gemilang about understanding the importance of the procedural process for migrant workers, they can add their understanding of the process procedurally.